Uncommon course of the ulnar artery through the pronator teres muscle - Vymazalova, K; Vargova, L; Joukal, M (JNMA; journal of the Nepal Medical Association, 2014)
In this paper, we describe a very rare variant in the course of the ulnar artery that we encountered in dissecting the right upper limb of a 74-year-old man. The ulnar artery arose standardly from the brachial artery in the cubital fossa. However, its ensuing course differed from the norm. The artery entered together with the ulnar vein and median nerve into the pronator canal (between the humeral and ulnar heads of the pronator teres). Further, the ulnar artery descended classically to the ulnar side of the forearm between the flexor carpi ulnaris and flexor digitorum superficialis. Knowledge of this variation in the course of the ulnar artery may have significance in clinical practice because accumulation of anatomical structures in the pronator canal could be a predisposing factor for the compression of nerve or blood vessels.
Keywords: arteria ulnaris; Anatomy, Comparative; anatomie topografická; lidé; vény; Veins; Anatomy, Regional; Forearm; anatomical variation; median nerve; pronator canal; pronator teres muscle; ulnar artery.; Median Nerve; anatomie srovnávací; Ulnar Artery; Male; Aged; předloktí; senioři; mužské pohlaví; nervus medianus; Humans